Pengaruh Suhu Dan Waktu Distilasi Terhadap Komposisi Kimia Asap Cair Dari Kulit Durian - Widiya Widiya; Idral Idral; Zultiniar Zultiniar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Purification of liquid smoke is very important for the safety of liquid smoke for preservative food. Distillation was done reduces carsinogenic compound such as tar and benzo(a)pyrene and determined 1st, 2nd, 3th grade of smoke liquid. The research was done using distillation process, with temperature and time variable. The results of GCMS analysis indicated no detected tar and benzo(a)pyrene. Maximum temperature to get of liquid smoke 1st grade at 125oC with distillation time was 30 minutes. At this condition value of acid, carbonyl and phenol were 20.53%, 27.05% and 0% Keywords: Pyrolysis, Distillation, Liquid Smoke